2019
DOI: 10.13005/bpj/1685
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Nutritional Value, Functional Properties and Pharmacological Application of Perilla (Perilla Frutescens L.)

Abstract: Perilla frutescens is an annual herb belonging to the mint family (Lamiaceae). It is majorly produced in countries like China, Japan, India, Thailand and Korea. Recently, Perilla plant is gaining more attention because of its medicinal benefits and phytochemical contents. The major phytochemical compounds reported in this species are phenolic compounds (Rosmarinic acid, caffeic acid, ferulic acid), flavonoids (luteolin, apigenin), Phytosterols, Tocopherols, Policosanols and Fatty acid. Perilla seed oil is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 75 publications
0
44
0
1
Order By: Relevance
“…The beneficial effects of almond, jojoba, soybean, and avocado oils have been confirmed in mammalian cells and in animal models [21]. Perilla oil has received considerable attention in the contexts the treatment of chronic diseases, such as cancer, diabetes, asthma, inflammatory, and cardiovascular diseases, because it contains fat, protein, vitamins, minerals, and phytochemicals [12]. As part of a research program aimed at identifying novel effects of perilla oil, we focused on the antiphotoaging effects of CPO on UV-treated skin fibroblasts and hairless mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of almond, jojoba, soybean, and avocado oils have been confirmed in mammalian cells and in animal models [21]. Perilla oil has received considerable attention in the contexts the treatment of chronic diseases, such as cancer, diabetes, asthma, inflammatory, and cardiovascular diseases, because it contains fat, protein, vitamins, minerals, and phytochemicals [12]. As part of a research program aimed at identifying novel effects of perilla oil, we focused on the antiphotoaging effects of CPO on UV-treated skin fibroblasts and hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…Perilla seeds and oil have attracted attention because they contain phytochemicals of therapeutic interest. Perilla oil contains fatty acids including linolenic acid (C18:3), linoleic acid (C18:2), palmitic acid (C16:1), oleic acid (C18:1) and stearic acid (C18:0) [11,12], and perilla seeds contain the phenolics rosmarinic acid, rosmarinic acid-3-O-glucoside, caffeic acid, ferulic acid, and caffeic acid-3-O-glucoside and the flavonoids apigenin, luteolin, and catechin [13]. In addition, perilla oil has been reported to have meaningful pharmacological effects in cancer, diabetes, asthma, microbial infectious diseases, inflammation, oxidative stress-related diseases, and cardiovascular disease [12,14], and perilla oil supplementation in diet was found to improve loperamide-induced constipation symptoms in albino rats and to enhanced cognitive function in elderly patients with mild cognitive impairment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Perilla (Perilla frutescens L. Briit) belongs to the Lamiaceae family (formely Labiateae) which consists of 235 genera and more than 700 species [76]. Perilla is an edible herb widely consumed in Asian countries such as China, Korea, Japan, and India.…”
Section: Perillamentioning
confidence: 99%
“…The leaves of perilla contain a range of bioactive phenolic molecules such as caffeic acid, catechin, chrysoeriol, ferrulic acid, luteolin, quercetin, and rosmarinic acid [78,79]. In particular, secondary metabolites such as rosmarinic acid and perillaldehyde (an essential oil constituent) have demonstrated potential to prevent a wide range of diseases particularly owing to their anti-diabetic, anti-depressant, anti-bacterial, anti-cancer, and antimicrobial properties [76]. Thus the concentrations of these two phytochemicals are crucial for their clinical and culinary applications.…”
Section: Perillamentioning
confidence: 99%
“…RA and CA have been reported to have many bioactive properties, such as antioxidant, antimicrobial, and antiinflammatory activity (Swamy et al, 2018;Colica et al, 2018), and were found to be major phenolic compounds in Perilla plants (Osakabe et al, 2002;Dhyani et al, 2019). Skowyra et al (2014) indicated that the concentration of TP in Perilla leaves was 22.67 mg GAE/g DW using 50% ethanol for extraction, Hong et al (2011) found a value of 12.15 mg GAE/g DW by extraction with 70% ethanol, and Chen et al (2019) reported the Perilla leaves possessed TP concentration of 50 mg GAE/g DW by extraction with acetone.…”
Section: Discussionmentioning
confidence: 99%